The air up there - Bacon, Kevin; Glaser, Paul M.; Apple, Max (Hollywood : Hollywood Pictures Home Video, 1995)
Desperate to recruit his American college team's next star player, assistant basketball coach Jimmy Dolan (Kevin Bacon) travels to Africa. Jimmy's target is a towering Winabi warrior, Saleh, who lives in a remote village and is next in line lead to his tribe. But Jimmy's plan quickly falls apart when his high-pressure recruiting tactics create hilarious turmoil and disruption among Saleh's family and the entire Winabi tribe
Keywords: Basketball stories -- Dramatization; Sport stories -- Dramatization